2010
DOI: 10.1186/1471-244x-10-27
|View full text |Cite
|
Sign up to set email alerts
|

The Beck Cognitive Insight Scale (BCIS): translation and validation of the Taiwanese version

Abstract: BackgroundOver the last few decades, research concerning the insight of patients with schizophrenia and its relationships with other clinical variables has been given much attention in the clinical setting. Since that time, a series of instruments assessing insight have been developed. The purpose of this study was to examine the reliability and validity of the Taiwanese version of the Beck Cognitive Insight Scale (BCIS). The BCIS is a self-administered instrument designed to evaluate cognitive processes that … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
39
1

Year Published

2010
2010
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 43 publications
(42 citation statements)
references
References 27 publications
(82 reference statements)
2
39
1
Order By: Relevance
“…12,[14][15][16][17][18][19] While the original article established a 2-factor solution for inpatients, the new studies have replicated this finding 14 and shown that the same solution fits outpatient, 12,16 first-episode, 17 and healthy control 15,18 samples, both in English [16][17][18] and nonEnglish 12,14,15,19 speakers. These studies have, additionally, employed differing analytic strategies: principle components factor analysis, 14,15 confirmatory factor analysis, 12,16,18 exploratory factor analysis, 19 and correlational analysis. 17 …”
Section: Factor Structuresupporting
confidence: 49%
“…12,[14][15][16][17][18][19] While the original article established a 2-factor solution for inpatients, the new studies have replicated this finding 14 and shown that the same solution fits outpatient, 12,16 first-episode, 17 and healthy control 15,18 samples, both in English [16][17][18] and nonEnglish 12,14,15,19 speakers. These studies have, additionally, employed differing analytic strategies: principle components factor analysis, 14,15 confirmatory factor analysis, 12,16,18 exploratory factor analysis, 19 and correlational analysis. 17 …”
Section: Factor Structuresupporting
confidence: 49%
“…Furthermore, when directly compared to healthy controls, psychiatric patients showed definitely lower levels of SR and global cognitive insight, but higher levels of SC (Warman et al, 2007;Kao & Liu, 2010;Martin et al, 2010), except for one study where no difference for any of the three BCIS indexes emerged (Engh et al, 2007).…”
Section: Introductionmentioning
confidence: 99%
“…A third study of an older population with a psychotic disorder achieved 0.08 loading for item 14, however removing it reportedly did not improve model fit and reasons why this item was poorly aligned were not discussed. In another study , items 12 and 14 aligned more strongly with self‐certainty. It may be the case that there is something within these items that does not strongly reflect the concept of self‐reflection, and this is more pronounced in a SUD population, particularly in treatment.…”
Section: Discussionmentioning
confidence: 99%